Sistem Informasi Geografis Pemetaan Persebaran Perceraian Faktor Ekonomi dan Pertengkaran di Kota Surakarta Tahun 2020-2023 - Dimas Aditya Saputra; Bambang Agus Herlambang; Ahmad Khoirul Anam (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This study aims to utilize QGIS as a spatial analysis tool to map the distribution of divorces based on economic factors and disputes in Surakarta City during the 2020–2023 period. The data used includes spatial data in the form of Surakarta City's administrative map in shapefile format and non-spatial data comprising the number of divorces obtained from BPS Surakarta. Non-spatial data were integrated into spatial data using the